POSTER TIGA RONDE: AN APPRAISAL ANALYSIS OF NEGATIVE COMMENTS ON TWITTER - Zulfa, Nadiyah; Herliani, Indah Kurnia (UC Journal: ELT, Linguistics and Literature Journal, 2023)
This paper discusses the negative comments on the tweets attacking the "tiga ronde'' poster during the student protest on April 11, 2022, that went viral on Twitter. This is a qualitative study, using the appraisal theory as an analytical method. The data collection is carried out by taking random tweets within the discourse of poster “tiga ronde”, which are then sorted into ten tweets as the appraising items. The appraising items were translated from Indonesian to English. We then looked for the word with the closest pragmatic meaning to the translated word in the semantic resources of the appraisal framework. Lastly, we categorized whether the appraising word is classified into effect, judgment, or appreciation. The study aims to understand the attitude of those negative comments. It is presumed that the intended meaning of the comments, whether it is an effect, judgment on the poster creator, or appreciation of the poster can give a better understanding of why they are used to attack the poster. The study reveals that a lot of anonymous accounts give judgment towards the creator’s behavior rather than appreciating the poster or expressing their feelings about the phenomenon.